Performance analysis of the EBARR protocol for wireless sensor networks. (1st January 2012) - Sumathi, R.; Srinivasan, R.
Critical events in wireless sensor network (WSN) applications demands QoS aware routing mechanism in order to deliver critical data more reliably with minimum latency to the sink or base station. The energy and the buffer are severely constrained resources of sensor nodes, they must be used efficiently during data delivery. This paper presents QoS aware routing protocol, namely the Energy-Buffer Aware Reliable Routing (EBARR) protocol which meets both challenges of reliability and timely delivery of critical data, along with efficient use of energy and buffer resources. The paper also includes performance analysis of the EBARR protocol, by modelling reliability and delay. In simulation, results are presented to compare the performance of the EBARR protocol with two other routing protocols in WSN, namely, multipath routing (MP) and minimum energy routing (MER).